2022
DOI: 10.1007/s40314-022-01940-0
|View full text |Cite
|
Sign up to set email alerts
|

Monic Chebyshev pseudospectral differentiation matrices for higher-order IVPs and BVPs: applications to certain types of real-life problems

Abstract: We introduce new differentiation matrices based on the pseudospectral collocation method. Monic Chebyshev polynomials (MCPs) were used as trial functions in differentiation matrices (D-matrices). Those matrices have been used to approximate the solutions of higher-order ordinary differential equations (H-ODEs). Two techniques will be used in this work. The first technique is a direct approximation of the H-ODE. While the second technique depends on transforming the H-ODE into a system of lower order ODEs. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Talaei and Asgar [41] and Chen et al [42] solved numerically this problem. In [41], the authors suggested an operational approach based on the Chelyshkov-collocation spectral method (CCSM) for the numerical solution of (34), while the authors in [42] applied the Haar wavelets method (HWM) for the numerical treatment of (34). The L 2 and L ∞ -errors of our presented method for different values of N with υ 1 = 0.25 and b = 2 are shown in Table 1.…”
Section: Illustrative Problems and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Talaei and Asgar [41] and Chen et al [42] solved numerically this problem. In [41], the authors suggested an operational approach based on the Chelyshkov-collocation spectral method (CCSM) for the numerical solution of (34), while the authors in [42] applied the Haar wavelets method (HWM) for the numerical treatment of (34). The L 2 and L ∞ -errors of our presented method for different values of N with υ 1 = 0.25 and b = 2 are shown in Table 1.…”
Section: Illustrative Problems and Comparisonsmentioning
confidence: 99%
“…In addition, they employed this class of polynomials to treat certain types of even-order BVPs. The authors in [33,34] handled some BVPs and IVP using the Chebyshev polynomials' first derivative.…”
Section: Introductionmentioning
confidence: 99%
“…These polynomials are used as basis functions in various papers when different spectral polynomials are applied. For example, the first kind of CPs are employed in [39] to treat some real-life problems. The same polynomials were utilized to solve some BVPs in [40].…”
Section: Introductionmentioning
confidence: 99%
“…The fundamental idea behind these methods is choosing suitable linear combinations of different special functions, often orthogonal polynomials. The spectral method uses different types of orthogonal polynomials, which are called basis functions, such as Chebyshev polynomials [9,10] or their derivatives [11], Legendre polynomials [12] or their derivatives [13][14][15], and Ultraspherical polynomials [16]. Spectral methods can solve ordinary differential equations by representing the unknown function in these equations as a finite series of well-known polynomials.…”
Section: Introductionmentioning
confidence: 99%